Longitudinal associations among mindfulness, cognitive reappraisal, expressive suppression, non-suicidal self injury, and suicidal ideation among Chinese adolescents - Yuan, Guangzhe Frank; Zhong, Shuang; Liu, Caimeng; Guo, Zhaoxin (Frontiers in Psychiatry, 2025)
IntroductionPrior research has shown that mindfulness may be as a protective factor against self-injurious behaviors and suicidal ideation. Yet, data on the associations between mindfulness, cognitive reappraisal, expressive suppression, non-suicidal self injury (NSSI), and suicidal ideation are limited.MethodThis study attempted to examine the potential mediational relationship between these variables using a two-wave follow-up data (T1 and T2; 6-month intervals) from a sample of 548 Chinese adolescents (Mage=16.10, SD=1.61, age range: 12–19 years; 51.1% boys).ResultsResults indicated that mindfulness at T1 was negatively associated with NSSI and suicidal ideation at T2. Cognitive reappraisal served as a mediator in the mindfulness-suicidal ideation relationship, while both cognitive reappraisal and expressive suppression functioned as parallel mediators in the mindfulness-NSSI relationship. Additionally, cognitive reappraisal and NSSI sequentially mediated the relationship between mindfulness and suicidal ideation.ConclusionsThese findings highlight the importance of fostering mindfulness and adaptive emotion regulation strategies in NSSI and suicide prevention programs for adolescents. Interventions that enhance mindfulness and promote cognitive reappraisal, while reducing reliance on expressive suppression, may effectively diminish self-injurious behaviors and suicidal thoughts among adolescents.